PENGARUH REPUTASI KAP, KOMITE AUDIT DAN PERGANTIAN AUDITOR TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN PEMODERASI CORPORATE GOVERNANCE (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Elisabeth Erintan Br. Purba; Edfan Darlis; Meilda Wiguna (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
This research to obtain empirical evidence about (1) corporate governance in moderating the influence of KAP reputation on integrity of financial statement, (2) corporate governance in moderating the influence of the audit committee to integrity of financial statement, (3) corporate governance in moderating the influence of auditor switching to integrity of financial statements. The object of this research is mining companies on the Indonesia Stock Exchange (BEI) in 2012-2016. In this research there were 42 companies as population, but based on the criteria of only 12 (twelve) companies so there were 60 samples in this research. The method used in this research is purposive sampling method. Data analysis techniques using multiple linear regression analysis model with SPSS 24 tools.The results showed that: (1) corporate governance was not able to moderate the influence of KAP reputation on the integrity of financial statements, (2) corporate governance moderate the influence of the audit committee on the integrity of financial statements, (3) corporate governance was not able to moderate the influence of auditor switching on the integrity of financial statements.